A macro-model of the Northern Ireland economy - Adele Bergin; Hailey Low; Stephen Millard; Akhilesh Verma (The Economic and Social Research Institute (ESRI), 2025)
This paper describes the structure and estimation of a structural macro-econometric model of the Northern Ireland economy. We show how it can be used to assess the potential impact of economic shocks and policy changes. Specifically, we have done so by examining the effects of shocks to UK monetary policy, Northern Ireland government spending, and the spillover impacts of an increase in Irish exports on the Northern Ireland and all-island economy. We find a weaker response of Northern Ireland output and inflation to a UK monetary policy shock vis-a-vis the rest of the United Kingdom. We also find that a 1 per cent increase in Northern Ireland government spending leads to a 0.3 per cent increase in Northern Ireland output with little effect on Northern Ireland inflation. Finally, we demonstrate that a 1 per cent temporary increase in demand for Irish exports results in a 0.15 per cent rise in Northern Ireland's output and a 0.3 per cent increase in the output of the all-island economy, before coming back to the baseline. However, in the case of a permanent shock, it leads to a permanent increase of 0.12 per cent in Northern Ireland's output. The modelling of these shocks by this new structural macro-economic model provides a useful illustration of the kinds of exercises that it can undertake.
Keywords: C51; C53; E17; 330; Macroeconomic Model; Northern Ireland economy; NiGEM